2022
DOI: 10.1021/acs.est.2c04528
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Avian Influenza Virus in Ambient Air in the Winter Habitats of Migratory Birds

Abstract: Outbreaks of avian influenza virus (AIV) have raised public concerns recently. Airborne AIV has been evaluated in live poultry markets and case farms; however, no study has discussed airborne AIV in ambient air in the winter habitats of migratory birds. Therefore, this study aimed to evaluate airborne AIV, specifically H5, H7, and H9, in a critical winter habitat of migratory birds and assess the factors influencing airborne AIV transmission in ambient air to provide novel insights into the epidemiology of avi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Air samplers were set up at a height of 1 m because this height was near the children’s breathing zone. Airborne influenza viruses were collected on 1.0 μm-pore polytetrafluoroethylene (Teflon; Pall Corporation, New York, NY, USA) membrane filters in disposable plastic cassettes at a sampling rate of 20 L/min for a 6-h sampling period (37 mm; HIBLOW SPP-25 GA, Techno Takatsuki, Osaka, Japan) [ 29 , 30 , 31 ]. The collected air samples were then transported at 4 °C to our laboratory and isolated within 3 days of collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Air samplers were set up at a height of 1 m because this height was near the children’s breathing zone. Airborne influenza viruses were collected on 1.0 μm-pore polytetrafluoroethylene (Teflon; Pall Corporation, New York, NY, USA) membrane filters in disposable plastic cassettes at a sampling rate of 20 L/min for a 6-h sampling period (37 mm; HIBLOW SPP-25 GA, Techno Takatsuki, Osaka, Japan) [ 29 , 30 , 31 ]. The collected air samples were then transported at 4 °C to our laboratory and isolated within 3 days of collection.…”
Section: Methodsmentioning
confidence: 99%
“…Samplers: National Institute for Occupational Safety and Health (NIOSH) bioaerosol sampler (BC251) with SKC AirChek XR5000 pump (SKC, Eighty Four, PA, USA) Sampling rates and time: 3.5 L/min for 30 min, and 6-13 air samplers per week. Sampling periods: October 2016 to June 2018 except during the summer holidays in 2017 (weeks [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Children who attend daycare centers are exposed to higher levels of infectious agents and air pollutants-including carbon monoxide (CO), carbon dioxide (CO 2 ), and ultrafine particles (UFPs)-than those who are cared for at home [12,13]. Studies have reported that children exposed to UFPs (aerodynamic diameter < 0.1 µm) have an increased risk of respiratory infection and hospital admission [14,15], and the amount of influenza virus found in the fraction of UFP S less than 0.25 um was 15% [16].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, wild birds are of paramount importance in the propagation of the pathogens. Specifically, migratory wild birds frequently traverse national and even intercontinental boundaries during migration or flight, serving as vectors for long-distance transmission of pathogenic viruses, bacteria, and parasites ( Envelope et al, 2021 ; Zhang et al, 2022 ). Furthermore, these pathogens undergo genetic evolution and reassortment mutations, leading to the emergence of mutated strains with altered pathogenicity and antigenicity.…”
Section: Introductionmentioning
confidence: 99%
“…faecal-oral route) (12,13,17,18). However, transmission via airborne particles may be relevant for some strains of AIV (e.g., H9N2) (13,14,(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Airborne transmission over short distances between birds has been demonstrated for some AIV strains (13,14,(19)(20)(21)(22)(23)(24)(25), and AIV has been detected in the air around wild birds in their natural habitat (14). However, in the context of the GsGD lineage of viruses, H5Nx HPAIV airborne transmission among avian species has not been conclusively demonstrated.…”
Section: Introductionmentioning
confidence: 99%